(untitled) (Jurnal Bahasa, 2002)
There is no language expression, especially a literary work, without metaphor and simile. I study this phenomenon in Malay poems before the 20th century. Dia seperti anjing is a simile, but dia anjing is a metaphor. And there are two types of simile. Ia seperti anjing is of type 1, a simple simile. Keadaannya tak ubah seperti kata pepatah.....is of type 2, a complex simile. A metaphor is of type 3. As indicated in the figure, it seems there is no simile of type 2 in the poems before the 20th century. In addition simile of the type 1 is more frequent compared to that of metaphor, the type, as in table 4. This due to the fact that a poem depends very much on its pattern. This is also responsible for the lack of simile of type 2. It is interesting to compare the phenomenon of simile and metaphor in the poem before the 20th century to that of the prose of the same period I discuss in another occasion. It is interesting to note that there are so many similes describing the beauty of a girl in the poems compared to thath in the prose of the same period. The presence of romantic elements in the poems is obvious.